2018
DOI: 10.1093/forsci/fxy042
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling the Tradeoff between Economic and Ecological Objectives in Habitat-Tree Selection: A Comparison between Students, Foresters, and Forestry Trainers

Abstract: Habitat trees provide microhabitats for many forest-related species, and thus habitat-tree retention is one of the main measures to integrate nature conservation objectives into forests managed for wood production. By setting aside habitat trees, forest managers have to solve a crucial tradeoff between economic and environmental benefits. Therefore, it is of major importance that trees with desired characteristics are retained as habitat trees. In this study, we analyze habitat-tree selection. Specifically, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…On the contrary, evaluations by humans are always subjective and reflect the subject's specific perspectives. Recent studies indicate that several factors, like education, or familiar management techniques and economic goals are inconsistently influencing tree selection practices, which may also largely depend on individual preferences [19,37,38]. Our finding that greener forests are perceived as richer in structure underlines the hypothesis that even forest experts unconsciously include a variety of factors in their rating of forest structures that may have no major relevance to it.…”
Section: Innovationsmentioning
confidence: 55%
See 2 more Smart Citations
“…On the contrary, evaluations by humans are always subjective and reflect the subject's specific perspectives. Recent studies indicate that several factors, like education, or familiar management techniques and economic goals are inconsistently influencing tree selection practices, which may also largely depend on individual preferences [19,37,38]. Our finding that greener forests are perceived as richer in structure underlines the hypothesis that even forest experts unconsciously include a variety of factors in their rating of forest structures that may have no major relevance to it.…”
Section: Innovationsmentioning
confidence: 55%
“…The large standard deviations in the expert ratings show that there is no consistent expert agreement on the quantification of forest structure. A study of Cosyns et al [19] on full inventoried tree-marking training sites has shown that forestry trainers made decisions on habitat tree selection that are more consistent than foresters' or students' choices, which supports the impact of participants' expertise on tree-selection. Nevertheless the overall agreement on which trees to select was low for all groups, which demonstrates the downside that this effect of expertise is limited.…”
Section: Innovationsmentioning
confidence: 92%
See 1 more Smart Citation
“…Only recently studies emerged, indicating i.a. that several factors related to individual's expertise can be important for tree selection (Cosyns et al 2018;Pommerening et al 2018;Spinelli et al 2016;Vitkova et al 2016). Correspondingly, empirical implementation research points to the crucial role of forest managers for the success of integrated nature conservation policies.…”
Section: Introductionmentioning
confidence: 99%
“…Analysing both quantitative data on tree characteristics and qualitative justifications of tree selection decisions together provides novel insights into how which trees are selected by different relevant professional groups. By doing so, this article goes beyond existing studies on tree selection which solely rely on quantitative data (Cosyns et al 2018;Pommerening et al 2018;Spinelli et al 2016;Vitkova et al 2016), and aims to also provide insights into the motivations for tree selection. The latter is specifically relevant for conservation policy to guide practical implementation of integrated forest management strategies.…”
Section: Introductionmentioning
confidence: 99%